A Study of Evaluation of Serum Uric Acid Level in Obesity (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Obesity is rapidly increasing worldwide. High serum uric acid has been documented to be associated with obesity. Previous studies have shown a relationship between hyperuricemia and obesity but evidence of such an association in population of Bangladesh is limited. Recent study has been shown that hyperuricemia is a predictor of non-communicable diseases and increase in mortality rate. The aim of this study was to observe the association of serum uric acid with obesity.Materials and methods: This cross-sectional study was carried out in the Department of Biochemistry in Chittagong Medical College and Outpatient Department of Endocrinology, Chittagong Medical College Hospital. One hundred and fifty (150) subjects ageing (18-55) years were included in this study by non-probability convenient sampling method. One hundred (100) subjects with obesity diagnosed by BMI enrolled as cases and fifty (50) normal weight were enrolled as controls. Important variables in this study were serum uric acid level, Fasting Lipid Profile, Fasting Plasma Glucose, Blood Pressure, BMI and Waist Circumference.Results: Hyperuricemia was found 45% among cases (c2, p< 0.001) and 8% in controls. Serum Triglyceride (TG), Total Cholesterol, Increased BMI, waist circumference were positively associated with obesity and Hyperuricemia. There was also positive correlation between serum uric acid with TG, TC, LDL-cholesterol, BMI and waist circumference and negative correlation between serum uric acid with fasting blood glucose and HDL-cholesterol. However this study did not find any significant association between serum uric acid with LDL and HDL cholesterol.Conclusion: The above mentioned findings suggest that, evaluation of serum uric acid level in obesity may provide data useful for the clinical course of diseases and further relevant research.JCMCTA 2022 ; 33 (2) : 89-94